Protocolo de aquisição de imagens 3D com smartphone para criação de banco virtual de narizes e reabilitação estético-funcional de pacientes mutilados nasais - Cabral, Bianca Nóbrega Lustosa (2020)
Individuals affected by nasal deformities have severe aesthetic, functional and psychosocial impairments. In this context, nasal rehabilitation using a prosthesis represents an important instrument for adapting and protecting the nasal cavity, and is also essential for aesthetic repair. The present study aimed to develop a 3D image acquisition protocol with a smartphone for creating a virtual bank of human noses and application in aesthetic-functional rehabilitation of nasal mutilates. From the 3D scanning of different intact faces, noses were extracted and stored virtually, forming a virtual bank of images of noses, allowing the mutilated patient to choose the best prosthetic option for their rehabilitation and visualize their face with nasal prosthetic work even before to be executed using the OrtogOnBlender software. A protocol was created for the acquisition of nasal models in 3D, with satisfactory quality, and its application in a mutilated patient, allowing the accomplishment of adaptation and aesthetic tests in a virtual way, shortening phases and optimizing the result in relation to the traditional process. This will make it possible to use a prosthetic rehabilitation technique with modern methods, which is quick, simple, comfortable and more accessible to the patient.